1995
DOI: 10.1093/clinids/20.2.457
|View full text |Cite
|
Sign up to set email alerts
|

Articular Aspergillosis: Case Report

Abstract: We present an unusual case of osteomyelitis of the tibia and septic arthritis of the knee caused by Aspergillus fumigatus in a renal transplant recipient. Although the characteristic joint involvement was present, the synovial fluid was initially sterile and contained numerous pyrophosphate crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The literature review yields only 12 reported cases of septic arthritis due to A. fumigatus and only one without systemic infection. Two cases in renal transplant recipients have been reported as arthrocentesis and corticosteroid complications 8 …”
Section: Discussionmentioning
confidence: 99%
“…The literature review yields only 12 reported cases of septic arthritis due to A. fumigatus and only one without systemic infection. Two cases in renal transplant recipients have been reported as arthrocentesis and corticosteroid complications 8 …”
Section: Discussionmentioning
confidence: 99%
“…Post‐operative cases of wound infection [87,138,139,141–143,297], peritonitis [297,298] and renal allograft infection [299] have also been described following solid‐organ transplantation. Although not always apparent, it is possible that some of these patients had occult foci from which the Aspergillus may have disseminated [299–325].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The published literature concerning FOAIs includes a heterogeneous spectrum of diseases with different prognoses [4][5][6]8,9,12,13,[15][16][17][19][20][21][22][23][24], and there is no standard treatment for patients with FOAIs. More specifically, there is no consensus on the optimum dose and duration of antifungal therapy, the value of combination antifungal therapy, or the timing and extent of adjunctive surgery [3,24].…”
Section: Discussionmentioning
confidence: 99%
“…There is a scarcity of literature concerning FOAIs, particularly in patients with cancer; most studies consist of case reports or small case series [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Therefore, the present study sought to define the characteristics of patients with FOAIs who received care at a comprehensive cancer centre during the past 10 years.…”
mentioning
confidence: 99%